THE ROLE OF TOURISTIC CITIES IN THE DEVELOPMENT OF TOURISM (Uzbek Scholar Journal, 2022)
This article discusses the importance of touristic cities, it is one of the touristic cities of Uzbekistan, in the field of tourism.